PERBANDINGAN ANTARA ECONOMIC VALUE ADDED (EVA) DENGAN RETURN ON ASSETS (ROA) DALAM MENILAI KINERJA KEUANGAN PERUSAHAAN: (Studi Kasus pada Saham IDX BUMN20 di Bursa Efek Indonesia) - Madina; Budiyanti, Hety; Nurman (Transpublika Publisher, 2022)
This study aims to compare the Economic Value Added (EVA) method with Return On Assets (ROA) in assessing the company's financial performance on IDX BUMN20 shares on the Indonesia Stock Exchange. Based on the results of the comparison discussion between EVA and ROA methods, it can be seen that there are differences in the two financial measuring instruments. This difference is caused because the ROA calculation does not pay attention to the cost of capital, while in the EVA method, the cost of capital is included in the calculation so that the EVA method is more profitable than ROA. However, the ROA method can be used as a supporter of EVA in assessing the company's financial performance.